2017
DOI: 10.1002/cssc.201701884
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Flow Synthesis of Supported Magnetic Iron Oxide Nanoparticles for Efficient Isoeugenol Conversion into Vanillin

Abstract: This work presents the synthesis of iron oxide nanocatalysts supported on mesoporous Al-SBA-15 by using a continuous-flow setup. The magnetic nanomaterials were tested as catalysts in the oxidative disruption of isoeugenol by using hydrogen peroxide as a green oxidant, featuring high activities (63-88 % conversion) and good selectivities to vanillin (44-68 %). The catalytic systems exhibited good magnetic properties when synthesized under continuous-flow conditions at temperatures not exceeding 190 °C. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Table S1 (Supplementary Materials) summarizes the materials synthesized. In particular, the employment of biomass residue as a carbon source presents outstanding advantages, since it allows the formation of a magnetic phase without employing other chemicals, such as propionic acid, commonly used for the synthesis of magnetic iron oxide [17]. Nanomaterials synthesized employing iron perchlorate and iron chloride did not show magnetic susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…Table S1 (Supplementary Materials) summarizes the materials synthesized. In particular, the employment of biomass residue as a carbon source presents outstanding advantages, since it allows the formation of a magnetic phase without employing other chemicals, such as propionic acid, commonly used for the synthesis of magnetic iron oxide [17]. Nanomaterials synthesized employing iron perchlorate and iron chloride did not show magnetic susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…9B, absorption bands characteristic of stretching vibration from 1430 to 1520 cm −1 are attributable to absorption of the benzene ring. 72 It can be concluded that the observed deactivation in NM-SCM catalytic activity might be due to adsorption of aromatics including benzene and other high-molecular-weight compounds as side products on the catalyst surface.…”
Section: Identification Of Intermediatesmentioning
confidence: 99%
“…Compounds such as eugenol, diphenylether and oligomers (calamenene) are generated avoiding the 100% conversion. This may due to the low acidity presented by the catalysts compared to traditional acid catalysts used in the same reaction [22].…”
Section: Catalytic Activitymentioning
confidence: 99%
“…These characteristics make mechanochemical milling a very attractive nanocatalysts synthesis technique. In addition, the required synthesis time is much shorter than in other synthesis techniques such as hydrothermal treatment [22]. There are several examples that have demonstrated the great potential of these mechanochemically synthesized NP.…”
mentioning
confidence: 99%